The THE EFFECTS OF EARNING PER SHARE AND CURRENT RATIO ON STOCK RETURN FOR FOOD AND BEVERAGE SECTOR COMPANIES LISTED ON THE IDX DURING THE COVID-19 PANDEMIC - Andi sayyidatun ufairah anto; Fenny Mika; Abdul Hamid Habbe; Nadhirah Nagu (SEAN Institute, 2022)
The aim of this study was to determine the effects of Earning Per Share and current ratio on stock return for food and beverage sector companies listed on the IDX during the COVID-19 Pandemic for the period of 2019-2021. The population of this research consists of the Food & Beverage Manufacturing Subsector companies listed on the Indonesia Stock Exchange for the year 2019-2021, a total of 35 firms. The study sample was collected using the approach of purposive sampling, which yielded 28 firms. Earning Per Share (EPS) and Current Ratio (CR) serve as independent variables, while stock returns serve as the dependent variable. According to the findings of this study, EPS has a positive effect on stock returns, but CR has no effect.